Doctoral Preparation in the Field of Special Education - Hensley, Gene.; Buck, Dorothy P., Eds.; Western Interstate Commission for Higher Education, Boulder, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The 7 selected papers in this pamphlet, which were presented at a conference on doctoral study in November 1968, are specifically concerned with the doctorate in special education. The unique factors of the special education doctoral program are discussed in the first paper. The second and third presentations deal with the variety of approaches to the education of the handicapped, and the educational objectives and curricular requirements of doctoral programs in special education. The fourth paper discusses the Joint Doctoral Degree Program in Special Education which began in 1967 between the University of California at Berkeley and San Francisco State College. The assessment of the personal characteristics and projected goals of a potential candidate as well as the university's resources for providing an adequate program and training environment are discussed as bases for the admissions guidelines presented in the fifth paper. A proposed tailor-made doctorate at the university of Washington is presented in the sixth paper. This program would match the needs of the field and the skills of the faculty with the talents and interests of the individual doctoral student. The seventh presentation deals with the future of doctoral programs in special education, with particular reference to roles, curricula, organization, and administration. (WM)
Educational level discussed: Higher Education.
ERIC Note: Selected papers of a conference on doctoral study, Tucson, Arizona, November 25-26, 1968.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academically Handicapped; Admission Criteria; Curriculum Development; Doctoral Programs; Educational Objectives; Graduate Study; Higher Education; Special Education